Can we predict neurological complications in patients with metastatic spinal tumors? - Jung, Chul; Shin, Hee Tae; Bae, Cho Rong; Lee, Joon Hee; Park, Jin Hoon; Cho, Jae-Hwan; Chee, Choong Guen; Jeon, Jae Yong (Frontiers in Oncology, 2025)
BackgroundPrevious studies primarily analyzed spinal cord injuries in patients with metastatic spinal tumors after such injuries had already occurred. This study aimed to determine whether clinical and radiological factors are associated with the occurrence and severity of newly developed spinal cord injuries within 1 year in patients with metastatic spinal tumors.MethodsWe retrospectively examined patients with metastatic spinal tumors who were referred to the Department of Rehabilitation Medicine between 2017 and 2021. Using patients’ clinical data and magnetic resonance imaging (MRI) findings, we investigated whether pain characteristics, Spinal Instability Neoplastic Score (SINS), and Epidural Spinal Cord Compression (ESCC) grades were associated with the occurrence and severity of spinal cord injuries within 1 year of MRI evaluation.ResultsAmong the 70 included patients, 40 developed spinal cord injuries. Multivariate analysis identified an ESCC grade 2 or 3 (high-grade ESCC) as the only significant predictor of spinal cord injury within 1 year (P = 0.016). Higher ESCC grades were also significantly associated with a shorter time to onset of spinal cord injuries (P = 0.003). Regarding the severity of spinal cord injuries, the total score and categories of SINS were significantly higher in the mild deficit group than in the moderate to severe deficit group (P = 0.024 and P = 0.049, respectively).ConclusionsIn patients with metastatic spinal tumors, high-grade ESCC was a significant predictor of spinal cord injury within 1 year and was associated with an earlier onset of spinal cord injury. Radicular pain and unstable spines based on SINS categories were also strongly associated with the occurrence of spinal cord injury. This study provides valuable insights for predicting 1-year functional outcomes and determining management strategies for spinal metastases.